Investigating Iranian English language teachers’ wellbeing across their career stages - Ashegh Navaie, Leila; Gholami, Javad; Mohammadnia, Zhila (Frontiers in Psychology, 2024)
This study aims to investigate the wellbeing role of teaching experience in the wellbeing of Iranian English as Foreign Language (EFL) teachers across their career stages in terms of teaching experienceby exploring the relationship between teaching experience and multiple dimensions of wellbeing. In this regard, Tthe study categorized teachers into three groups based on their experience: novice, experienced, and highly experienced. The study Uusing ed a quantitative and cross-sectional survey design, this study and Utilizing employed a validated scale, the study measuredto measure psychological wellbeing, positive perception about self and life, goal setting and time management, and positive relationships among teachers. Using a convenience sampling procedure, A total of 182 Iranian EFL teachers participated in the study, representing varying age ranges, teaching experience, and employment status. The data was collected through an online survey within a month and underwent descriptive and inferential statistical analysis analyses using SPSS software. The results revealed significant differences in the wellbeing of language teachers across among the three experience groups.More specifically, Nnovice teachers scored lower in various dimensions of wellbeing compared towellbeing dimensions than experienced and highly experienced teachers. These findings emphasize the importance of considering career stages when investigating teachers' professional wellbeing. The findings also contribute to a deeper understanding of the relationship between teaching experience and wellbeing, with implications for supporting the wellbeing of EFL teachers' wellbeing and informing educational policies and practices. The results of the studystudy results are discussed, and the related implications are provided for running professional development courses that to enhance teachers' wellbeing.